Innovation and Managerial Incentives: A Tale of Two Systems - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2004)
This paper describes R&D competition between a managerial firm and an entrepreneurial one, in a Cournot market. It is shown that a manager interested in output expansion exerts higher R&D efforts, yielding productive efficiency as compared to the performance of a strictly profit-seeking firm. This may ultimately yield monopoly power for the managerial firm, if technological spillovers in the industry are low enough.
Keywords: 330; Innovationsmanagement; Innovationswettbewerb; Führungskräfte; Entrepreneurship-Ansatz; Spillover-Effekt; Produktivität; Theorie